Predictors of functional outcome in musculoskeletal healthcare: An umbrella review. (13th October 2019) - Burgess, Roanna; Mansell, Gemma; Bishop, Annette; Lewis, Martyn; Hill, Jonathan
Abstract: Background: Multiple cohort and systematic review studies exist, reporting independent predictive factors associated with outcome in musculoskeletal populations. These studies have found evidence for a number of "generic" factors that have been shown to predict outcome across musculoskeletal patient cohorts. This review provides a higher level review of the evidence with a focus on generic patient factors associated with functional musculoskeletal outcome with a view to informing predictive modelling. Objectives: (a) Identify patient factors found to have evidence to support their association with functional outcome, and (b) review these findings across body areas/conditions to identify generic predictive factors. Databases and Data Treatment: Electronic databases of MEDLINE, AMED, EMBASE, CINAHL and Cochrane were searched for eligible studies. Two reviewers independently extracted data and assessed quality using an established checklist for umbrella reviews. Results: Twenty‐one systematic reviews met inclusion criteria, all were of moderate/high quality. Six independent predictors were found to have strong evidence of association with worse musculoskeletal functional outcome across anatomical body sites (worse baseline function, higher symptom/pain severity, worse mental well‐being, more comorbidities, older age and higher body mass index). Longer duration of symptoms, worse pain coping, presence of workers compensation, lower vitality and lower education were also found to have moderate evidence of association with worse functional outcome across body sites. Conclusions: This study identifies a number of factors associated with musculoskeletal functional outcome. The generic predictive factors identified should be considered for inclusion into musculoskeletal prognostic models, including models used for case‐mix‐adjustment of patient reported outcome measure data. Significance: This article identifies "generic" patient factors that predict functional outcome (measured using Patient Reported Outcome Measures (PROMs)) across musculoskeletal conditions. Findings provide support for the development and content of generic musculoskeletal prognostic models including models used to case‐mix adjust PROM data for baseline complexity. Generic musculoskeletal models and functional PROMs would facilitate more feasible comparison and benchmarking of musculoskeletal services in order to identify variation and address health inequalities.